Influence of early growth on interplant yield variability of the two main yam species in West Africa - (:unkn) unknown (My University, 2015)
In West Africa, shifting cultivation using the slash and burn technique is the traditional yam cropping system. Current knowledge is insufficient to elaborate and recommend sustainable alternatives to this cropping system, which threatens the environment. Recent studies have shown unexplained interplant yield variability to be an important brake on the improvement of yam production system that hinders intensification attempts. In this context, the objective of the thesis was to study yield interplant variability of the two main yam species (Dioscorea alata and D. rotundata) and more specifically to quantify this variability, to identify its causes and to estimate its physiological, agronomic and economic consequences. A set of 11 experiments carried out between 2006 and 2009 at two locations in Benin, enabled us to demonstrate that interplant variability of yam yield is much higher than that of similar tuber crops, such as potato (CV > 40% and CV < 20%, respectively) and that it appears at an early growth stage. Causes of this variability were identified and their direct and indirect effects were quantified using a Bayesian network. At common planting densities (0.4-1 plants m-²), these results showed that there was no competition between plants. In contrast, the use of traditional planting material introduced important initial variability between individual plants, especially in the observed emergence date and seed-tuber weight. We developed a plant model to simulate yam growth as a function of factors affecting yield variability and yam development as a function of daily photoperiod and temperature. The model gives good estimates of observed plant yield. Observations and simulations both demonstrate that delayed emergence and lower seed-tuber quality (lower weight) lead to a slower vegetative growth, unduly early tuber initiation and finally a lower yield. In com
Keywords: African Research